Quantum software testing: State of the art. Issue 4 (24th December 2021) - García de la Barrera, Antonio; García‐Rodríguez de Guzmán, Ignacio; Polo, Macario; Piattini, Mario
Abstract: Quantum computing is expected to exponentially outperform classic computing on a broad set of problems, including encryption, machine learning, and simulations. It has an impact yet to explore on all software lifecycle's processes and techniques. Testing quantum software raises a significant number of challenges due to the unique properties of quantum physics—such as superposition and entanglementand the stochastic behavior of quantum systems. It is, therefore, an open research issue. In this work, we offer a systematic mapping study of quantum software testing engineering, presenting a comprehensive view of the current state of the art. The main identified trends in testing techniques are (1) the statistic approaches based on repeated measurements and (2) the use of Hoare‐like logics to reason about software correctness. Another relevant line of research is reversible circuit testing, which is partially applicable to quantum software unitary testing. Finally, we have observed a flourishing of secondary studies and frameworks supporting testing processes from 2018 onwards. Abstract : In this paper, we conduct a systematic mapping study of quantum software testing engineering, presenting a comprehensive view of the current state of the art. The main trends we have identified in testing techniques are (1) the statistic approaches based on repeated measurements and (2) the use of Hoare‐like logic to reason about software correctness. We discuss the results and provide a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis to outline future lines of work for both researchers and practitioners.